Pengaruh Penggunaan Digital Supply Chain Platform Terintegrasi Berbasis Fintech dan Logistik serta Financial Self-Efficacy terhadap Keberlanjutan Bisnis UMKM dengan Literasi Digital sebagai Variabel Moderasi - Muhammad Farrel Adi Pratama (Indo Publishing, 2026)
This study aims to analyze the effect of Digital Supply Chain Platform integrated with Fintech and Logistics and Financial Self-Efficacy on MSME Business Sustainability with Digital Literacy as a moderating variable. The research employs a quantitative explanatory method with 408 e-commerce MSME respondents in the Jabodetabek area. Data analysis uses Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that the use of Digital Supply Chain Platform has a positive and significant effect on MSME Business Sustainability (β=0.295; p<0.001), and Financial Self-Efficacy also has a positive and significant effect (β=0.256; p<0.001). Digital Literacy moderates the relationship between Digital Supply Chain Platform and Business Sustainability (β=0.130; p=0.027), indicating that higher digital literacy strengthens the impact of platform utilization on business sustainability. However, Digital Literacy does not moderate the relationship between Financial Self-Efficacy and Business Sustainability (β=-0.039; p=0.548), suggesting that financial self-efficacy operates autonomously regardless of digital competence. The PLS-SEM model explains 29.5% of the variance in MSME Business Sustainability (R²=0.295) with an SRMR value of 0.032, indicating a very good model fit. This study concludes that business sustainability in the digital era results from the interaction between technological resources, psychological-financial capabilities, and digital competencies that collectively form the foundation of long-term business competitiveness and resilience.